Printable zinc-manganese(IV)oxide batteries - Kim, Jun Seob. (2010)
To answer the technological gap of printable batteries in the world of printed electronics, development of techniques to fabricate printable alkaline Zn-MnO2 batteries are pursued in this project. Construction of the cell is based on, and improves on previous work. Effort is concentrated in the refinement of the cathode. To study the effect of nano-crystals of MnO2 on the electrochemical performance of the Zn-MnO2 system, a variety of hydrothermal methods for synthesis of nano-crystalline MnO2 are studied. Synthesised powders are characterised by XRD and SEM, and then fabricated into working cells for discharge performance for comparison against commercial MnO2. Performance is analysed by open circuit potential, discharge potential, energy and power densities, and overall discharge profile.